2016
DOI: 10.1155/2016/7825432
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Understanding How Heavy Metal Pollution Triggers Gastric Cancer

Abstract: With the development of industrialization and urbanization, heavy metals contamination has become a major environmental problem. Numerous investigations have revealed an association between heavy metal exposure and the incidence and mortality of gastric cancer. The mechanisms of heavy metals (lead, cadmium, mercury, chromium, and arsenic) contamination leading to gastric cancer are concluded in this review. There are four main potential mechanisms: (1) Heavy metals disrupt the gastric mucosal barrier by decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 74 publications
1
68
1
5
Order By: Relevance
“…[1,11] Numerous studies have described the effects of heavy metals on the occurrence of gastric cancer [2,7,12]. Studies of other authors confirmed our study too, which shows that vegetables and fruit grown in soil contaminated with heavy metals can cause stomach carcinoma [12,13]. Our study has found an increase in the number of patients operated for gastric adenocarcinoma in industrial municipalities of Tuzla, Živinice, Lukavac and Gračanica.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…[1,11] Numerous studies have described the effects of heavy metals on the occurrence of gastric cancer [2,7,12]. Studies of other authors confirmed our study too, which shows that vegetables and fruit grown in soil contaminated with heavy metals can cause stomach carcinoma [12,13]. Our study has found an increase in the number of patients operated for gastric adenocarcinoma in industrial municipalities of Tuzla, Živinice, Lukavac and Gračanica.…”
Section: Discussionsupporting
confidence: 86%
“…There was an increase in the number of operated patients compared to the total number of respondents who mostly consumed vegetables from the areas contaminated by the floods. Other studies have also confirmed the effects of heavy metals on the occurrence of stomach carcinoma [13,14].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Bioaccumulation of arsenic and cadmium in the human body can cause damage to the liver, kidney, lung and immune system [5]. Therefore, it is essential to establish sensitive and accurate methods for arsenic and cadmium determination.…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
“…Los metales pesados son elementos como Pb, Hg, Cu, Ni, Cr, Tl, Se, Cd, Zn, Al, Br y As, con una densidad al menos cinco veces mayor a la del agua, se distinguen por su persistencia en el medioambiente (Tchounwou et al, 2012;Yuan et al, 2016). Por ser elementos de la corteza terrestre, no se pueden destruir ni degradar, su biodisponibilidad y toxicidad dependen completamente de su comportamiento químico (Bulgariu y Bulgariu, 2012;Pretorius et al, 2001).…”
Section: Introductionunclassified